Al-Kalimāt Żātu Ashlin ‘Arabi fī Mu’jam (KBBI) wa Al-Istifādah Minhā fī Ta’līm Mahārah Al-Kalām Harf (I) Namudzajan - Murni Cahyati; Arif Taufikurrohman (Mauriduna: Journal of Islamic Studies, 2021)
تهدف هذه الدراسة إلى معرفة الكلمات الإندونيسية ذات أصل عربي في قاموس اللغة الإندونيسية الكبير (KBBI) بحرف (I) وتحليلها، ومعرفة التغيرات التي حصل على اللغة العربية بعد انتقالها إلى اللغة الإندونيسية من الناحية اللفظية والمعنوية، وكيفية الاستفادة من هذه الكلمات في تعليم مهارة الكلام للإندونيسيين. المنهج الذي سلكته الباحثة في هذه الدراسة هو المنهج الوصفي التحليلي، حيث إن بهذا المنهج استطاعت الباحثة تحليل الكلمات الإندونيسية ذات أصل عربي في قاموسها وكيفية الاستفادة منها في تعليم مهارة الكلام. فمن خلال هذه الدراسة وجدت الباحثة126 (مائة وستة وعشرين) كلمة عربية ذات أصل عربي في قاموس اللغة الإندونيسية الكبير (KBBI) بحرف (I)، ومن هذه الكلمات يمكن تقسيمها إلى أربعة تقسيمات، الأول: الكلمات العربية التي بقيت معانيها في اللغة الإندونيسية، والثاني: الكلمات العربية التي اتسعت معانيها في اللغة الإندونيسية، والثالث: الكلمات العربية التي ضاقت معانيها في اللغة الإندونيسية، والرابع: الكلمات العربية التي انتقلت معانيها في اللغة الإندونيسية. كما أنها أثبتت إمكانية الاستفادة من هذه الكلمات في تعليم مهارة الكلام. This study aims to find out Indonesian vocabulary from Arabic in the large Indonesian dictionary (KBBI) in letter (I) and analyze it, and to find out the changes in arabic after the verbal and moral transition to indonesian, and how to use them. The vocabulary in teaching speaking skills to Indonesian. The approach that researchers took in this study is a descriptive analytic approach, because with this approach researchers can analyze Indonesian vocabulary from Arabic in their distionaries and how to use it in teaching speaking skills. Through this study, researches found 126 (one hundred twenty-six) arabic vocabularies originating from arabic in the large Indonesian dictionary (KBBI) with the letter (I), and from these words can be divided into four divisions, the first: vocabulary Arabic, the meaning of which remains in Indonesian, and the second: Arabic vocabulary whose meaning extends in indonesian, and third: arabic vocabulary whose meaning narrows in Indonesian, and fouth: arabic vocabulary whose meaning is different from meaning in language Indonesia. It also shows that the vocabulary can be used to teach speaking skills.